Characteristics of Local Government as Zakat (tithe) Collector in Aceh Province, Indonesia - Dodik Siswantoro (Sharia and Law Faculty, 2017)
This paper aims to analyze the characteristics of local government as zakat collector in Aceh, Indonesia. In Aceh province, zakat can be collected by the government as original regional income in the local budget. This study uses primary and secondary data gathered from an in-depth interview and the audit board’s database. The interview was conducted in June 2013 in Aceh at BaitulMal and local administrative offices. Only 6 out of 23 local governments collected zakat. Data is analyzed based on descriptive statistics and crosstab analysis. The paper provides evidence that most local governments did not collect zakat as original regional income and present the expenditure accordingly and explicitly. It is also found that the special allocation fund has a significant negative correlation with zakat collection. While significant differences are evidenced between local governments that collect zakat on original regional income, budget surplus, asset, fixed asset and debt. Local governments that have not collected zakat yet as original regional income in their local budget can learn from regions that have. Some specific characteristics may influence regions that have collected zakat in their regional budgets.